Funding women entrepreneurs How to empower growth - Fackelmann, Surya (European Investment Bank, 2020)
Intervention is needed to improve women-led companies' access to finance. In a recent study, EIB's InnovFin Advisory assessed the availability of finance for women-owned and managed companies in Europe as compared to the United States. While women-led companies account for only a small portion of financing deals and investment flows, their share is growing. Nevertheless, structural inequalities and persistent biases continue to distort the funding environment. The study puts forth a number of innovative finance and policy recommendations. Restarting the EU economy after the coronavirus pandemic provides a unique opportunity to tackle gender barriers to finance.